PENGEMBANGAN GAMES EDUKASI BERBANTUAN WORDWALL PADA MUATAN IPAS TOPIK KEKAYAAN BUDAYA INDONESIA KELAS IV SEKOLAH DASAR NEGERI 41 PONTIANAK UTARA - Nurhamzah, Dede; Kresnadi, Hery; Ghasya, Dyoty Auliya Vilda (Universitas Tanjungpura, 2025)
In general, this research aims to develop educational games on wordwall website for IPAS learning content at 4th grade class at SD Negeri 41 Pontianak Utara wich is eligible to assist learning activities in Merdeka Curriculum. The present study utilizes the RD (Research and Development) method, employing the ADDIE model. The data of research was obtained form one class at SD Negeri 41 Pontianak Utara, totaling 27 students, and assisted by 2 validators consisting of an expert of media and an expert of material. The research also involved a 4th grade teacher. The techniques of collection of data are observation, interviews, and questionnaires. The findings of the study indicated that the development of wordwall educational games on IPAS learning content for the